Assessment of the dynamics of sensory perception of Wagyu beef strip loin prepared with different cooking methods and fattening periods using the temporal dominance of sensations. Issue 11 (26th September 2019) - Watanabe, Genya; Motoyama, Michiyo; Orita, Kazue; Takita, Keigo; Aonuma, Tatsuya; Nakajima, Ikuyo; Tajima, Atsushi; Abe, Atsuko; Sasaki, Keisuke
Abstract: In this study, we assessed the relative sensory perception of Wagyu beef using temporal dominance of sensations (TDS), which is a dynamic sensory method that captures the "dominance of sensation" throughout food consumption. In addition, we checked the integrity of the TDS by comparing the TDS results with a physicochemical analysis. Strip loins were obtained from 24‐ and 28‐month‐old Japanese Black cattle ("Wagyu") and were cooked by grilling ( yakiniku ) or boiling ( shabu‐shabu ). Temporal dominance of sensations was then used to evaluate the four types of samples. "Tender and/or soft, " "juicy, " "dry, " "fat melting, " "fat taste, " "umami, " "sweet taste, " and "butter odor" were dominant in at least one of the sample types, with the yakiniku cooking method highlighting texture‐ and fat‐related sensory characteristics, and the shabu‐shabu cooking method highlighting flavor‐related sensory characteristics. In addition, beef obtained from the 24‐month‐old Wagyu was significantly more "dry" than that of the 28‐month‐old cattle, reflecting their different cooking loss. Temporal dominance of sensations successfully demonstrated the dominant sensory perceptions of Wagyu beef prepared with different cooking methods and fattening periods. Abstract : This article demonstrates the dynamic sensory perceptions of Wagyu beef prepared with different cooking methods and fattening periods by temporal dominance of sensations (TDS). The TDS method demonstrated the dominant sensory characteristics that contribute to the dynamic sensory perception of Wagyu beef and that there are differences in the sensory perception of meat samples depending on both the cooking method and fattening period.